PENGENALAN PEMBERIAN LATIHAN PROBLEM BASED LEARNING PADA BUKU TEKS BAHASA INGGRIS “LETS COMMUNICATE ACTIVELY” KEPADA GURU DAN SISWA DI SMPN 31 PADANG - Elmiati Elmiati Elmiati; SUHARNI SUHARNI SUHARNI; MUHAMAD KHAIRI IKHSAN (STKIP PGRI Sumatera Barat, 2021)
ABSTRACT The purpose of this research is implementing of English textbook of Problem Based Learning for Junior High School Class VII as the implementation of Curriculum 2013. This research is the continuation of the previous research about evaluation of English Textbook Entitled When English Rings the Bell for Junior High School class VII as the Implementation of Curriculum 2013. Participants of this research were teachers and students at SMP N 31 Padang. These activities consist of two terms. At the first term of this activity, Researchers introduced models of excercises problem based learning by explaining the materials related to problem based learning. Then, at the second activity of this term was teams of this research guide the teachers to create Lesson Plan of Problem based learning. This lesson plan created by the teacher, then team submitted to be analyzed and revised by the teachers. Keywords: Model, problem based learning ABSTRAK Tujuan dari kegiatan ini adalah menerapkan latihan problem based learning untuk siswa kelas VII SMP sebagai salah satu implementasi kurikulum 2013. Kegiatan ini merupakan lanjutan dari pengabdian sebelumnya tentang evaluasi buku teks Bahasa Inggris SMP kelas VII implementasi kurikulum 2013. Peserta yang terlibat dalam pengabdian ini adalah guru-guru dan siswa di SMPN 31 Padang. Pengabdian ini terdiri dari dua bahagian. Bahagian pertama merupakan tahapan pemberian model latihan berbasis problem kepada siswa-siswa dan guru. Sedangkan pada tahapan kedua adalah penugasan pembuatan RPP kepada Guru-guru SMPN 31 Padang. RPP tersebut dikumpulkan kepada tim pengadian. Tim pengabdian memeriksanya dan memberikan saran perbaikan kepada guru-guru tersebut. Keywords; : Model, problem based learning